Factors associated with the functional health and well-being of Singapore residents living with the covid-19 endemic - Zhilian Huang; Kangwei Zeng; Hwee Pin Phua; Chia Siong Wong; Mark I-Cheng Chen (Journal of Global Antimicrobial Resistance)
INTRODUCTION: Globally, reports have shown conflicting impacts of COVID-19 on health-related quality of life (HR-QOL). We assessed the population-level effect of COVID-19 on HR-QOL among Singapore residents through a prospective COVID-19 serological cohort study that included mild and subclinical COVID-19 infections. METHODS: We measured participants' functional health and well-being using Rand's Short-Form Health Survey (SF-36) at their fifth(December 22–January 23) and sixth(August–October 23) visits. Outcome measures were the SF-36 physical health (PHC) and mental health (MHC) component scores. Participants were considered not infected with COVID-19 if they were anti-N non-reactive and had never reported COVID-19 infections during visits. We used linear mixed models to analyze panel data. RESULTS: We analyzed 1194/1203 participants aged 6-90 years. Factors negatively associated with PHC scores include aged >25 years [-5.77(-7.95, 3.95)], being female [-4.30(-5.97, -2.63)], non-tertiary educated [-2.60(-4.38, -0.83)] and having pre-existing medical condition(s) [-4.65(-6.75, -2.55)]. Factors negatively associated with MHC scores include aged <25 years [-3.50(-6.50, -0.50)], being female [-4.07(-5.97, -2.63)], and currently smoking [-8.87(-14.18, -3.55)]. After adjusting for these, mean PHC and MHC were significantly lower among participants with COVID-19 ≤80 days before assessment [PHC: -5.03(-7.90, -2.16)] [MHC: -4.14(-7.38, -1.45)] and those who were anti-N reactive without reporting COVID-19 infections [PHC: -2.59(-4.97, -0.21)] [MHC: -2.81(-5.55, -0.06)], compared with participants not infected with COVID-19. CONCLUSIONS: COVID-19 had a measurable impact, particularly PHC, on the HR-QOL of community dwelling residents. The effects seemed to attenuate over time from infection, but changes in the HR-QOL of individuals should ideally be measured over longer periods.